Interaksi Umat Islam Indonesia Terhadap Lansia (Studi Living Qur’an) - Mohammad Rohmanan (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Interaction of Indonesian Muslims towards the Elderly (Study of the Living Qur'an)Through the Qur'an and Hadith, Islam upholds the honor of the elderly. The attitudes, words, and deeds of the prophet Muhammad SAW were the actualization of the values of the Qur'an, so that he was dubbed